GABAergic synapses between auditory efferent neurons and type II spiral ganglion afferent neurons in the mouse cochlea - Julia L. Bachman; Siân R. Kitcher; Lucas G. Vattino; Holly J. Beaulac; M. Grace Chaves; Israel Hernandez Rivera; Eleonora Katz; Carolina Wedemeyer; Catherine J. C. Weisz (Proceedings of the National Academy of Sciences, 2025)
Cochlear outer hair cells (OHCs) are electromotile and implicated in amplification of responses to sound that enhance sound sensitivity and frequency tuning. They send afferent information through glutamatergic synapses onto type II spiral ganglion neurons (SGNs). These synapses are weaker than those from cochlear inner hair cells onto type I SGN, suggesting that type II SGNs respond only to intense sound levels. OHCs also receive efferent innervation from medial olivocochlear (MOC) neurons. MOC neurons are cholinergic yet inhibit OHCs due to the functional coupling of alpha9/alpha10 nicotinic acetylcholine receptors (nAChRs) to calcium-activated SK potassium channels. The resulting hyperpolarization reduces OHC activity-evoked electromotility and is implicated in cochlear gain control, protection against acoustic trauma, and attention. MOC neurons also label for markers of GABA and GABA synthesis. GABA B autoreceptor (GABA B R) activation on MOC terminals has been demonstrated to reduce ACh release, confirming important negative feedback roles. However, the full complement of GABAergic activity in the cochlea is not currently understood, including mechanisms of GABA release from MOC axons, whether GABA diffuses from MOC axons to other postsynaptic cells, and the location and function of GABA A receptors (GABA A Rs). We used optical neurotransmitter detection, immunohistochemistry, and patch-clamp electrophysiology to demonstrate that in addition to presynaptic GABA B autoreceptor activation, MOC efferent terminals release GABA onto type II SGN afferent dendrites with postsynaptic activity mediated by GABA A Rs. This synapse may have roles including developmental regulation of cochlear innervation, fine-tuning of OHC activity, or providing feedback to the brain about MOC and OHC activity.